Sports activities at a young age decrease hypertension risk—The J‐Fit+ study. Issue 12 (27th June 2022) - Kumagai, Hiroshi; Miyamoto‐Mikami, Eri; Someya, Yuki; Kidokoro, Tetsuhiro; Miller, Brendan; Kumagai, Michi Emma; Yoshioka, Masaki; Choi, Youngju; Tagawa, Kaname; Maeda, Seiji; Kohmura, Yoshimitsu; Suzuki, Koya; et al.
Abstract: This study aimed to assess (1) blood pressure between young, current athletes, and non‐athletes early in life; (2) hypertension prevalence between former athletes and the general population later in life; and (3) understand the mechanisms between exercise training and hypertension risks in the form of DNA methylation. Study 1: A total of 354 young male participants, including current athletes, underwent blood pressure assessment. Study 2: The prevalence of hypertension in 1269 male former athletes was compared with that in the Japanese general population. Current and former athletes were divided into three groups: endurance‐, mixed‐, and sprint/power‐group. Study 3: We analyzed the effect of aerobic‐ or resistance‐training on DNA methylation patterns using publicly available datasets to explore the possible underlying mechanisms. In young, current athletes, the mixed‐ and sprint/power‐group exhibited higher systolic blood pressure, and all groups exhibited higher pulse pressure than non‐athletes. In contrast, the prevalence of hypertension in former athletes was significantly lower in all groups than in the general population. Compared to endurance‐group (reference), adjusted‐hazard ratios for the incidence of hypertension among mixed‐ and sprint/power‐group were 1.24 (0.87–1.84) and 1.50 (1.04–2.23), respectively. Moreover, aerobic‐ and resistance‐training commonly modified over 3000 DNA methylation sites in skeletal muscle, and these were suggested to be associated with cardiovascular function‐related pathways. These findings suggest that the high blood pressure induced by exercise training at a young age does not influence the development of future hypertension. Furthermore, previous exercise training experiences at a young age could decrease the risk of future hypertension. Abstract : High blood pressure induced by exercise training at a young age is an adaptation to exercise training and does not influence the development of future hypertension. Furthermore, previous exercise training experiences at a young age could decrease the risk of future hypertension.